Kain Tenun Lotis Sebagai Warisan Budaya Lokal Di Kecamatan Nunkolo (TTS) - Jesycha Marling Nenabu; Hywa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Woven fabric is a legacy of Indonesian culture, particularly the customs of Nunkolo District, South Central Timor Regency. Ikat weaving holds significant artistic, historical, and philosophical value. The technique of making ikat woven fabric involves weaving warp and weft threads to create unique patterns and motifs. Lotis woven fabric from South Central Timor Regency is unique in its patterns, motifs, and color combinations, reflecting the cultural identity of the local community. With the passage of time and the lack of attention to preserving cultural traditions, local interest in traditional Lotis woven fabric has declined. Therefore, the color imagery in Lotis woven fabric is crucial for maintaining the authenticity of the motifs, preserving their beauty and color imagery, and preserving their cultural values. This effort strengthens the region’s cultural identity and encourages the younger generation to appreciate the heritage of their ancestors.